2018
DOI: 10.1021/acscatal.8b01969
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering of a Carbon Nitride–Graphene Oxide–Molecular Ni Catalyst Hybrid for Enhanced Photocatalytic Activity

Abstract: Carbon nitrides (CNx) are a promising class of photocatalyst for fuel and chemical synthesis as they are non-toxic and readily synthesized at a low cost. This study reports the enhanced photocatalytic activity for simultaneous alcohol oxidation and proton reduction when graphene oxide (GO) or reduced graphene oxide (RGO) is employed as an interlayer between a cyanamide-functionalized melon-type carbon nitride (NCN CNx) and a phosphonated Ni-bis(diphosphine) H2-evolution catalyst (NiP). Introduction of the GO/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 127 publications
2
50
0
Order By: Relevance
“…The electron accumulation in polymeric carbon nitride photocatalysts is known to be one of the major bottlenecks in light-driven hydrogen evolution, 47,48 and has been typically addressed by deposition of Pt, [48][49][50] Ni-based molecular catalysts, [51][52][53] or enzymes. 11,54 We investigated polymeric carbon nitride Figure S10.…”
Section: Discussionmentioning
confidence: 99%
“…The electron accumulation in polymeric carbon nitride photocatalysts is known to be one of the major bottlenecks in light-driven hydrogen evolution, 47,48 and has been typically addressed by deposition of Pt, [48][49][50] Ni-based molecular catalysts, [51][52][53] or enzymes. 11,54 We investigated polymeric carbon nitride Figure S10.…”
Section: Discussionmentioning
confidence: 99%
“…The a-cel-CD/NiP system provides a benchmark activity of 13 450 mmol H 2 (g CDs ) À1 h À1 ( Figure S3, Table S5). [10,11,14] The a-cel-CDs display a maximum internal quantum efficiency (IQE at l = 360 nm, I = 4.05 mW cm À2 ) of 11.4 %, which compares favorably with g-N-CDs (5.3 %) and a-CDs (1.4 %). [10b] Future improvements in the development of the CDs should focus on high IQEs in the visible region.…”
mentioning
confidence: 99%
“…The DUMCN and UMCN samples both have two diffraction peaks, %12.9 and 27.6 corresponding to the (100) and (002) peaks of GCN, respectively, which indicate that the introduction of N-vacancy did not alter the crystal structure of GCN. [39] The two peaks can be assigned to the in-plane repeat trigonal nitrogen linkage of tri-s-triazine units and interlayer stacking of the conjugated aromatic C─N heterocycles system. [28,37,40] It is shown that the peaks of DUMCN sample have a much-reduced intensity and become broad, which may attribute to the reduced length of interlayer periodicity and a larger spacing between the DUMCN layers result from the CN triple bond and N-vacancy.…”
Section: Catalyst Characterizationmentioning
confidence: 99%